新加坡同志空间 ：1970年代以来国家与同志群体的权力交涉场域 = Gay spaces in Singapore : the power struggle Arena between the state and the gay community since the 1970s - 曾家盛 Chan, Jason Kah Seng (Nanyang Technological University, 2021)
在新加坡国家政府所推崇的异性恋霸权意识形态下，处于边缘的同志群体往往必须与主流的异性恋群体进行空间上的争夺。空间是政治的属地，也是权力生产的结果。握有掌控权的国家在一定程度上有着掌管空间的使用以及其使用者。因此为了在国家内享有属于自己的空间，新加坡的同志群体必须与国家进行一系列的权力交涉。本论文将主要通过米歇尔·福柯（Michel Foucault）的空间理论概念来研究从1970年代以来，新加坡的同志群体如何在服务于主流异性恋群体的空间内塑造出属于他们自己的同志空间，而在这些众多的同志空间里头又如何发生了与国家之间的权力交涉。其中，更会以芳林公园作为主要讨论空间，阐述此空间的多元性，从70年代的“同志渔场”到如今同志群体能合法地为自己的权益发声的空间。 Under the heteronormative ideology in which the Singaporean state has been promoting, the marginalised gay community has to contest for space with the mainstream heterosexual community. Space is not just a result of the production of power, but is also a political locale. The state which wields the greatest power in the country decides how the space is used and who the users of the space are. Therefore, in order to have a space for themselves, the gay community have no choice but to engage in a power struggle with the state. Using the analytical framework of space provided by Michel Foucault, this thesis aims to study the various gay spaces in Singapore since the 1970s by outlining the power struggle with the state that occurs in these spaces. It eventually focuses on Hong Lim Park, which is seen as a place with diversified meanings, from a gay cruising spot in the 1970s to the 1980s, to a symbol of gay activism since Pink Dot started in 2009.